IMPROVING STUDENTS™ READING COMPREHENSION IN DESCRIPTIVE TEXT THROUGH ANTICIPATION GUIDE - Nasution, Maya Puspita (Universitas Negeri Medan, 2014)
Abstract This study concerrns with improving students™ reading comprehension in descriptive text through anticipation guide.The objective was to investigate improvement of students™ reading comprehension by applying anticipation guide. This research was conducted by using action research method. The subject of the study was grade VII students of SMP SWASTA TAMAN HARAPAN MEDAN totalling to 30 students. They were taught reading comprehension by anticipation guide. The instruments for collecting data were quantitative data and qualitative data (observation sheet and questionnaire sheet). Based on the test score of quantitative data, students™ score kept improving in every evaluation. In the orientation test the mean was 51, in the cycle I test the mean was 67,6. In the cycle II test the mean was 79,6. The percentage of orientation test was 16,6 %, cycle I test was 30 % and cycle II test was 73,3 %. The finding of the research showed that applying anticipation guide significantly improved students™ reading comprehension. The qualitative data show that the students were more interested and motivated on reading comprehension through anticipation guide. It is suggested that teachers should apply anticipation guide as one of strategy to improve students™ reading comprehension.